ARMH1 is a novel marker associated with poor pediatric AML outcomes that affect the fatty acid synthesis and cell cycle pathways - Bakhtiari, Mojtaba; Jordan, Sean C.; Mumme, Hope L.; Sharma, Richa; Shanmugam, Mala; Bhasin, Swati S.; Bhasin, Manoj (Frontiers in Oncology, 2024)
IntroductionDespite remarkable progress in Pediatric Acute Myeloid Leukemia (pAML) treatments, the relapsed disease remains difficult to treat, making it pertinent to identify novel biomarkers of prognostic/therapeutic significance.Material and methodsBone marrow samples from 21 pAML patients were analyzed using single cell RNA sequencing, functional assays with ARMH1 knockdown and overexpression were performed in leukemia cell lines to evaluate impact on proliferation and migration, and chemotherapy sensitivity. Mitochondrial function was assessed via Seahorse assay, ARMH1 interacting proteins were studied using co-immunoprecipitation. Bulk RNA-seq was performed on ARMH1knockdown and over expressing cell lines to evaluate the pathways and networks impacted by ARMH1.ResultsOur data shows that ARMH1, a novel cancer-associated gene, is highly expressed in the malignant blast cells of multiple pediatric hematologic malignancies, including AML, T/B-ALL, and T/B-MPAL. Notably, ARMH1 expression is significantly elevated in blast cells of patients who relapsed or have a high-risk cytogenetic profile (MLL) compared to standard-risk (RUNX1, inv (16)). ARMH1 expression is also significantly correlated with the pediatric leukemia stem cell score of 6 genes (LSC6) associated with poor outcomes. Perturbation of ARMH1 (knockdown and overexpression) in leukemia cell lines significantly impacted cell proliferation and migration. The RNA-sequencing analysis on multiple ARMH1 knockdown and overexpressing cell lines established an association with mitochondrial fatty acid synthesis and cell cycle pathways.The investigation of the mitochondrial matrix shows that pharmacological inhibition of a key enzyme in fatty acid synthesis regulation, CPT1A, resulted in ARMH1 downregulation. ARMH1 knockdown also led to a significant reduction in CPT1A and ATP production as well as Oxygen Consumption Rate. Our data indicates that downregulating ARMH1 impacts cell proliferation by reducing key cell cycle regulators such as CDCA7 and EZH2. Further, we also established that ARMH1 is a key physical interactant of EZH2, associated with multiple cancers.ConclusionOur findings underscore further evaluation of ARMH1 as a potential candidate for targeted therapies and stratification of aggressive pAML to improve outcomes.